Influence of surgical stabilization of clavicle fractures in multiply-injured patients with thoracic trauma - Helge Eberbach (Nature Portfolio, 2021)
Abstract Thoracic trauma has decisive influence on the outcome of multiply-injured patients and is often associated with clavicle fractures. The affected patients are prone to lung dysfunction and multiple organ failure. A multi-center, retrospective analysis of patient records documented in the TraumaRegister DGU was performed to assess the influence of surgical stabilization of clavicle fractures in patients with thoracic trauma. A total of 3,209 patients were included in the analysis. In 1362 patients (42%) the clavicle fracture was treated operatively after 7.1 ± 5.3 days. Surgically treated patients had a significant reduction in lung failure (p = 0.013, OR = 0.74), multiple organ failure (p = 0.001, OR = 0.64), intubation time (p = 0.004; −1.81 days) and length of hospital stay (p = 0.014; −1.51 days) compared to non-operative treatment. Moreover, surgical fixation of the clavicle within five days following hospital admission significantly reduced the rates of lung failure (p = 0.01, OR = 0.62), multiple organ failure (p = 0.01, OR = 0.59) and length of hospital stay (p = 0.01; −2.1 days). Based on our results, multiply-injured patients with thoracic trauma and concomitant clavicle fracture may benefit significantly from surgical stabilization of a clavicle fracture, especially when surgery is performed within the first five days after hospital admission.